L’antiféminisme de gauche – un syndrome révisionniste - Dixon, Marlene (Revue PréfiX, 2024)
Même si la misogynie et les agressions sexuelles sont des problèmes bien connus et depuis longtemps dénoncés par des féministes militant dans les réseaux de gauche et d’extrême-gauche, les textes d’analyse sur l’antiféminisme de gauche restent relativement rares dans la vaste production d’études sur l’antiféminisme en général
Keywords: 1800-1899; 1900-1999; amériques; antiféminisme; approches et analyses; capitalisme; communisme; cours; discipline; droits des femmes*; féminisme matérialiste; gauche; patriarcat; pol5185; premier cycle; prolétariat; préFiX; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; traduction; travail; violences; états-unis

Recherches sur la transitude au Québec: entre absence et exploitation des savoirs trans - Clark Pignedoli; Maxime Faddoul (Genre, Sexualité et Société, 2019)
En suivant l’approche méthodologique de l’autoethnographie, cet article se penche sur la question de l’exploitation des personnes trans en tant que travailleur·se·s précaires de l’université néolibérale. On met en relief la double dynamique d’effacement et d’exploitation des personnes trans « en tant que trans », en soulignant qu’au sein du biocapitalisme, la transitude produit de la valeur qui peut être extraite afin de donner un nouveau souffle aux processus d’accumulation de la richesse. Les conditions de travail des personnes trans dans le domaine de la recherche sont ainsi surdéterminées par ces nouveaux mécanismes d’extractivisme. En guise de conclusion, on partage certaines stratégies de résistance pour renverser cette double dynamique.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; amériques; approches et analyses; biolcapitalisme; canada; capitalisme; cours; discipline; exploitation; premier cycle; périodes historiques; québec; régions géographiques; résistance; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques; trans; travail; travail gratuit; travail social; université; violences; études de genres

Épistémologies du Sud, pensées et féminismes décoloniaux latino-américains - Coenga-Oliveira, Danielle (Revue Possibles, 2019)
Keywords: approches et analyses; capitalisme; cours; discipline; féminisme décolonial; histoire et politique; pol4212; premier cycle; science politique; science politique et droit; sciences humaines; sofia; système colonial; systèmes d'oppressions; thématiques; violences; épistémologie

The Institution of Gender-Based Asylum and Epistemic Injustice: A Structural Limit - Sertler, Ezgi (Feminist Philosophy Quarterly, 2018)
One of the recent attempts to explore epistemic dimensions of forced displacement focuses on the institution of gender-based asylum and hopes to detect forms of epistemic injustice within assessments of gender related asylum applications. Following this attempt, I aim in this paper to demonstrate how the institution of gender-based asylum is structured to produce epistemic injustice at least in the forms of testimonial injustice and contributory injustice. This structural limit becomes visible when we realize how the institution of asylum is formed to provide legitimacy to the institutional comfort the respective migration courts and boards enjoy. This institutional comfort afforded to migration boards and courts by the existing asylum regimes in the current order of nation-states leads to a systemic prioritization of state actors’ epistemic resources rather than that of applicants, which, in turn, results in epistemic injustice and impacts the determination of applicants’ refugee status.
Keywords: approches et analyses; capitalisme; confort institutionnel; cours; cycles supérieurs; discipline; fem9000; injustices testimoniales; injustices épistémiques; institutions; migration; philosophie; politiques migratoires; racisme; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Epistemic Injustice and Illness - Kidd, Ian James; Carel, Havi (Journal of Applied Philosophy, 2017)
This article analyses the phenomenon of epistemic injustice within contemporary healthcare. We begin by detailing the persistent complaints patients make about their testimonial frustration and hermeneutical marginalization, and the negative impact this has on their care. We offer an epistemic analysis of this problem using Miranda Fricker’s account of epistemic injustice. We detail two types of epistemic injustice, testimonial and hermeneutical, and identify the negative stereotypes and structural features of modern healthcare practices that generate them. We claim that these stereotypes and structural features render ill persons especially vulnerable to these two types of epistemic injustice. We end by proposing five avenues for further work on epistemic injustice in healthcare.
Keywords: amériques; approches et analyses; capacitisme; capitalisme; care; corps; cours; cycles supérieurs; discipline; europe; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; philosophie; racisme; royaume-uni; régions géographiques; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

La portée réparatrice et réconciliatrice de la Commission de vérité et réconciliation du Canada - Jaccoud, Mylène (Recherches amérindiennes au Québec, 2016)
Cet article examine les potentialités réparatrices et réconciliatrices de la Commission de vérité et réconciliation (CVR) qui a été mise en place au Canada de 2008 à 2015 en réponse aux traumatismes vécus par les autochtones dans les pensionnats. L’auteure conclut que ces potentialités sont relativement limitées. Les principales limites tiennent à l’absence d’un espace de dialogue entre les victimes et les responsables, à une centration sur les narratifs traumatiques des victimes mais aussi à une conception dépolitisée du principe de la réconciliation. La CVR du Canada n’a pas inscrit la décolonisation comme vecteur de réconciliation mais a préféré s’engager dans la voie d’une pacification des relations entre les peuples. Or, l’auteure soutient que la réconciliation entre les peuples autochtones et l’État nécessite de dépasser les gestes de guérison et de réparation matérielle ou symbolique. La décolonisation des institutions, la redistribution des territoires et une réforme constitutionnelle en profondeur restent les seules avenues possibles pour parvenir à réconcilier avec ses oppresseurs un peuple victime d’un génocide culturel.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; capitalisme; commission de vérité et réconciliation; cours; criminologie; discipline; droits des personnes autochtones; féminisme décolonial; histoire et politique; justice réparatrice; justice sociale; peuples autochtones; pol4102; premier cycle; périodes historiques; racisme; réconciliation; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; violences

Epistemic Justice as a Virtue of Social Institutions - Anderson, Elizabeth (Social Epistemology, 2012)
In Epistemic injustice, Miranda Fricker makes a tremendous contribution to theorizing the intersection of social epistemology with theories of justice. Theories of justice often take as their object of assessment either interpersonal transactions (specific exchanges between persons) or particular institutions. They may also take a more comprehensive perspective in assessing systems of institutions. This systemic perspective may enable control of the cumulative effects of millions of individual transactions that cannot be controlled at the individual or institutional levels. This is true not only with respect to the overall distribution of such goods as income and wealth, but also with respect to the goods of testimonial and hermeneutical justice. Cognitive biases that may be difficult for even epistemically virtuous individuals to correct on their own may be more susceptible to correction if we focus on the principles that should govern our systems of testimonial gathering and assessment. Hence, while Fricker’s focus on individual epistemic virtue is important, we also need to consider what epistemic justice as a virtue of social systems would require. My paper will indicate some directions forward on this front, focusing on the need for integration of diverse institutions and persons engaged in inquiry.
Keywords: approches et analyses; biais cognitifs; capitalisme; cours; cycles supérieurs; discipline; droits des personnes; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; inégalités; justice épistémique; philosophie; sciences humaines; systèmes d'oppressions; thématiques; violences; éthique

Whose `Special Treatment'? Heterosexism and the Problems with Liberalism - Brickell, Chris (Sexualities, 2001)
This article examines the circulation of heterosexist positions within several recent New Zealand media texts. It argues that a recent form of discourse engages liberal language and assumptions in ways that support the privileged position of heterosexuality and the marginalization of homosexuality. The examples given highlight not only the tenor of some recent representations of homosexuality, but also some problems within liberalism. Most notable of these are liberalism's individualism and its failure to recognize the systemic nature of hierarchical power relationships and the constituting of lesbian and gay subjectivities within these relationships. These problems allow liberalism to play an active part in processes of domination and subordination.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; capitalisme; cours; discipline; discours médiatique; histoire; hétérosexisme; libéralisme; nouvelle-zélande; océanie; premier cycle; périodes historiques; rapports de domination; régions géographiques; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques; violences

The death of nature: Women, ecology and the scientific revolution - Merchant, Carolyn (New York : Harper & Row, 1983)
Un examen de la révolution scientifique qui montre comment la vision mécaniste du monde de la science moderne a sanctionné l'exploitation de la nature, l'expansion commerciale sans retenue et un nouvel ordre socio-économique qui subordonne les femmes.
Keywords: approches et analyses; capitalisme; discipline; environnement; histoire; histoire des sciences; histoire et politique; incontournable; patriarcat; philosophie; progrès; projet charge mentale; santé; sciences humaines; systèmes d'oppressions; thématiques; violences; violences envers la nature; violences envers les femmes*; écoféminisme